KOLERASI JUMLAH LEUKOSIT TERHADAP KADAR CRP PADA PENDERITA PENYAKIT TUBERKULOSIS - Bastian Darwin; Meyrita Birka Yolanda (jurnal kesehatan terapan sains dan teknologi, 2023)
Introduction: Tuberculosis is one of the most common infectious diseases in the community with a percentage of 80% caused by Acid Resistant Bacillus (BTA), namely the bacterium Mycobacterium tuberculosis. Leukocytes act as an immune system or kill germs and diseases that are in the human bloodstream. In addition to leukocytes, there are CRP parameters that help fight tuberculosis infection, namely by releasing various pro-inflammatory cytokines and bacterial invasion occurs which then induces liver cells to synthesize acute phase proteins such as CRP which will increase sharply for a few moments, inflammation will occur during the systemic inflammatory process. Purpose: This study aims to determine the correlation between leukocyte count and CRP levels in tuberculosis patients. Research Method: This research was conducted in the Hematology Laboratory of the Muhammadiyah Palembang Institute of Health Sciences and Technology in March-April 2021. This type of research is Analytical Descriptive research with a cross sectional approach. Data were analyzed using Spearmen's correlation test. Results: This study had an average leukocyte count of 4.85 cells/µL, CRP examination results with an average value of 9.60 mg/L and Spearman's correlation test with p = 0.113. Conclusion: There is no correlation between leukocyte count and CRP levels in tuberculosis patients.